Impacts of Sanitation Practices on Human Development: A Decade-Long Analysis of the Malang District - Angga Dheta Shirajjudin Aji; Sapta Suhardono; I Wayan Koko Suryawan; Wisnu Prayogo (Universitas Muhammadiyah Ponorogo, 2024)
This study explores the influence of various sanitation practices on the Human Development Index (HDI) in the Malang District from 2011 to 2020. Employing a multiple linear regression analysis, the research examines the relationship between the HDI and five critical sanitation practices: access to wastewater treatment plants, open defecation prevalence, septic tank usage, and direct waste disposal into water bodies and onto land. Secondary data was sourced from the Badan Pusat Statistika of Malang District, ensuring robust and authoritative information spanning over a decade. Preliminary diagnostics were performed to affirm the data's suitability for regression analysis. The results indicated a significant negative impact of direct disposal into water bodies on HDI, emphasizing the critical role of effective waste management practices in promoting human development. The study underscores the need for integrated policy approaches that address sanitation infrastructure improvements, environmental protection, and education on public health practices. This paper contributes to the literature by quantifying the effects of sanitation on human development over an extended period. It offers evidence-based recommendations for policymakers to support sustainable development goals in the region.